Analisis Program Pengendalian Tuberkulosis dengan Strategi DOTS di Puskesmas Manutapen Kupang - Belinna Eslly Mayopu; Fiane de Fretes; Kristiani Desimina Tauho (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: Tuberculosis (Tb) is a global challenge for public health problems, including Indonesia. Kupang is the city in East Nusa Tenggara (NTT) that has the highest number of Tb cases with a Success Rate (SR) about 85% in 2017. However, in 2018 the SR rate decreased to about 81%. Adherence to taking medication can have an effect on increasing the SR rate. In NTT, had many cases of withdrawal problems caused by Tb patient not taking medication regularly. The Tb control Program in NTT is based on the Directly Observed Treatment Short Course (DOTS) Strategy that focuses on case finding and cure rates. The five components of DOTS are: 1) Political commitment 2) Case finding 3) Standard treatment 4) Drug management and availability systems 5) Monitoring, recording and reporting system. The purpose of this study is to analyze the implementation of DOTS strategy in Manutapen Public Health Center (Puskesmas)Methods: This study was a descriptive qualitative method with used in-depth interviews. The main informants were three health officer participants from the Puskesmas. Triangulation informants were one participant of the Disease Control and Prevention Program of the Kupang Health Officer, one PMO participant, and one Tb patient participant.Result: Tb control with DOTS strategy encountered obstacles including a lack of political commitment related to funding new Tb cases, the high workload made the Tb officers unable to monitor the patients, and unreported cases.Conclusion: Tuberculosis control program with the DOTS strategy in Manutapen Public Health Center kupang was not optimalized.